2001
DOI: 10.1007/s100380170062
|View full text |Cite
|
Sign up to set email alerts
|

Two mutations of the Gsα gene in two Japanese patients with sporadic pseudohypoparathyroidism type Ia

Abstract: Pseudohypoparathyroidism Ia (PHP-Ia), is an inherited disease with clinical hypoparathyroidism caused by parathyroid hormone resistance (PTH), and shows the phenotype of Albright hereditary osteodystrophy (AHO), including short stature, obesity, round face, brachydactyly, and subcutaneous ossification. This disease is caused by mutation that inactivates the α-subunit of Gs, the stimulatory regulator of adenylyl cyclase. Here, a novel frameshift mutation (delG at codon 88) in exon 4, and a missense mutation (R2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…We obtained the approval of the study by the institutional ethical committee of Kansai Medical University and Matsubara Municipal Hospital and the parents gave their written informed consent for DNA analysis. The 13 exons and exon-intron boundaries of the Gsα gene were amplified by polymerase chain reaction (PCR) using oligonucleotide primers as described in a previous report [14]. Direct sequencing from both 5' and 3' ends of the amplified genomic DNA fragments revealed the substitution of histidine for arginine at position 385 (R385H) in exon 13 of the GNAS gene (Fig.…”
Section: A Report Of Casementioning
confidence: 99%
“…We obtained the approval of the study by the institutional ethical committee of Kansai Medical University and Matsubara Municipal Hospital and the parents gave their written informed consent for DNA analysis. The 13 exons and exon-intron boundaries of the Gsα gene were amplified by polymerase chain reaction (PCR) using oligonucleotide primers as described in a previous report [14]. Direct sequencing from both 5' and 3' ends of the amplified genomic DNA fragments revealed the substitution of histidine for arginine at position 385 (R385H) in exon 13 of the GNAS gene (Fig.…”
Section: A Report Of Casementioning
confidence: 99%
“…1B) was missed until recently. The R231H mutation in exon 9 of GNAS, reported in previous PHP1a patients [Farfel et al, 1996;Ishikawa et al, 2001], was identified in this family. Both sons are full heterozygotes and the mother shows somatic mosaicism.…”
Section: Introductionmentioning
confidence: 76%
“…Designations of patients are identical to that used in original case reports [Farfel et al, 1996;Ishikawa et al, 2001].…”
Section: Methodsmentioning
confidence: 99%
“…Of the 13 patients who were reported to have elevated serum TSH concentrations (10, 11, 13 -15, 17 -19, 22, 23) eight were treated with thyroid hormone (10,13,15,17,19). Four had low thyroid hormone levels (10,13,14,17), whereas in four other individuals the levels were normal (11,15,22,23). In the remaining five cases thyroid hormone levels were not mentioned (18,19).…”
Section: Discussionmentioning
confidence: 99%